Fluoroethylene Carbonate as Electrolyte Additive for Improving the electrochemical performances of High-Capacity Li1.16[Mn0.75Ni0.25]0.84O2 Material. (20th June 2015) - Li, Yang; Lian, Fang; Ma, Leilei; Liu, Chunlan; Yang, Lin; Sun, Xiaomeng; Chou, Kuochih
Graphical abstract: Highlights: FEC is introduced as electrolyte additive in the lithium-rich layered oxide cathode system. DFT calculation results indicate the preferential reaction of FEC on cathode surface during charging. A more conductive and thermal stable SEI film can be formed on the cathode surface with FEC as additive. Abstract: The effects of a small amount of fluoroethylene carbonate (C3 H3 FO3 or FEC) on the electrochemical performance of lithium-rich layered oxide cathode Li1.16 [Mn0.75 Ni0.25 ]0.84 O2 have been focused herein. When 1 vol.% or 2 vol.% FEC was introduced into the electrolyte, cycling performance and rate capability of Li1.16 [Mn0.75 Ni0.25 ]0.84 O2 have been improved, and the initial irreversible capacity (Cirr ) loss has been lessened by suppressing the parasitic side reactions between cathode and electrolyte. However, excess FEC (5% in volume) will lead to the decreased lithium transference number (tLi+ ), large concentration polarization and the reduced discharge capacity especially at high current. DFT calculations indicate that FEC enhances the anti-oxidation ability of the electrolyte system, and the preferential accumulation and reaction of FEC near cathode during charging due to the strong coordination between FEC and PF6 − anion. The results from electrochemical impedance spectroscopy (EIS), X-ray photoelectron spectroscopy (XPS) and differential scanning calorimetry (DSC) measures indicate that a more stable SEI film has been formed on the cathode surface with FEC as additive, which leads to the suppression of the electrolyte aggressive decomposition and the enhancement of thermal stability.